Sofrimento moral e clima ético entre enfermeiros hospitalares - Bernardi, Camila Milene Soares (2022)
Hospital nurses are faced with ethical issues/conflicts in their care practice, which depending on their deliberation process, may or may not cause them moral distress. Its general objective was to analyze the association between moral distress and the perception of ethical climate among nurses in hospital environments. The study was developed in two stages: one with a quantitative approach and the other a qualitative one. The quantitative stage was carried out with 269 nurses of a university hospital in the South region of Brazil, through the access to the database of the matrix project entitled "Moral distress in hospital nurses: what is its relation with ethical climate and burnout?", using sociodemographic and work variables, the Brazilian Scale of Moral Distress in Nurses and the Hospital Ethical Climate Survey - Brazilian version. For data analysis, descriptive statistics, Mann-Whitney test, and Poisson regression were employed. Thus, it was found that the highest intensity and frequency of moral distress was related to the factor Working conditions, while the lowest was related to the factor Defense of values and rights. Furthermore, moral distress was associated with the variables general negative ethical climate, employment relationship, and intention to quit. In the qualitative stage, semi-structured interviews were conducted with 20 nurses working in the psychiatric units, emergency room, surgical clinic, and obstetric center of the same university hospital. Through textual discourse analysis, two categories emerged: Repercussions of the negative ethical climate and the occurrence of moral distress; and Facilitators for the positive ethical climate and moral acting. Thus, this study made it possible to analyze the main repercussions resulting from moral distress in nurses, which are more evident when the perception of the ethical climate is negative. It is also suggested that improving the ethical climate through implementations of interventions to reduce moral distress in nurses. This study is in accordance with the ethical precepts proposed by resolution 466/2012.